Linguistic Structure and Hypnolinguistic Mechanisms of Neuro-Linguistic Programming Discourse in Shaping Students' Speech and Design Thinking in Senior High Schools - Masniati Murni Ritonga (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Language functions not only as a medium of communication but also as a cognitive mechanism shaping thought, behavior, and problem-solving abilities. In Indonesian secondary schools, students are often exposed to negative linguistic environments characterized by verbal bullying, authoritarian classroom discourse, and discouraging communication, potentially affecting their self-concept and creative thinking. This study investigates the linguistic structures and hypnolinguistic mechanisms of Neuro-Linguistic Programming (NLP) discourse in shaping students' speech and Design Thinking skills. A qualitative interdisciplinary case study with embedded pre- and post-intervention comparisons was conducted over 16 weeks at SMA Islam Plus Adzkia, West Java. Participants included 30 students purposively selected based on high exposure to verbal trauma and eight educators. Data were collected through classroom observations, audio-recorded interactions, discourse transcriptions, self-talk protocols, Design Thinking project assessments, and observations of neurolinguistic communication markers. Data analysis integrated Critical Discourse Analysis, Transformational-Generative Syntax, cognitive semantics, and speech act theory. Findings indicate that NLP-based discourse intervention transformed classroom communication by reducing directive and authoritarian expressions while increasing presuppositional, sensory-based, and supportive linguistic patterns. Students demonstrated reduced self-deprecating language and increased expressions of agency, confidence, and figurative language use. Improvements were also observed in speech fluency, communication confidence, and linguistic competence. Design Thinking performance improved across all dimensions, particularly during ideation, suggesting that constructive linguistic environments facilitate creative problem-solving and innovation. Correlation analysis revealed a strong positive relationship between linguistic transformation and Design Thinking performance, indicating that supportive discourse promotes cognitive and communicative development. These findings underscore the value of integrating NLP-informed communication strategies into classroom practice to strengthen students' linguistic confidence, higher-order thinking skills, and innovative pedagogy.